Risk, information, and trust in the food chain : factors explaining consumer willingness to pay - Latvala, Terhi (Centmapress, 2010)
This paper analysed factors contributing to consumers f willingness to pay (WTP) for increased quality information. The empirical scope of the study was restricted to beef, because the beef labelling system enables reliable tracing of quality attributes. The results showed that consumer perceptions of specific risks in food partly explain their WTP. Also negative experiences heard from other people increased the probability of WTP. Trust seems to be extremely significant factor in WTP models. This study implies that the majority of the respondents trust the food safety authorities and the co ]operation of all stakeholders in the food chain
Keywords: Ma; ruoka; elintarvikkeet; turvallisuus; riskit; naudanliha; food; safety; beef; risks; trust; information; willingness to pay; luottamus; informaatio; maksuhalukkuus